Development of Project based Statistics e-Module with Scratch Assistance to Improve Students’ Computational Thinking Skills - Findayani, Ni Kadek; Suparta, I Nengah; Sariyasa, Sariyasa (FKIP Universitas Lampung, 2023)
Abstract: This study aims to develop a project-based e-module to improve the computational thinking skills in learning statistics. The research subjects were 15 of eight-grade students in class A and 32 students in class E. The research has succeeded in developing the learning module assisted by Scratch which found to be valid and effective in improving students' mathematical computational thinking skills. This is supported by the validation result of 3.10 with a valid category. Student responses to the e-module obtained an average score of 3.57 in the very practical category. The teacher's response to the e-module obtained a score of 3.40 in the practical category. The effectivity test of the module toward students' mathematical problem solving ability found that n-gain score was 68.93. These results conform that the developed e-module meets the valid, practical and effective criteria. Keywords: e-module, project based learning, computational thinking. Abstrak: Penelitian ini bertujuan untuk melakukan pengembangan e-modul project-based learning berbantuan scratch untuk meningkatkan keterampilan berpikir komputasi siswa SMP Neger 2 Kuta. Subjek penelitian adalah siswa kelas VIII A yang berjumlah 15 orang serta kelas VIII E yang berjumlah 32 orang. Penelitian yang telah dilaksanakan pada kelas VIII SMP Negeri 2 Kuta ini telah berhasil mengembangkan perangkat pembelajaran meliputi E-Modul berorientasi PjBL berbantuan Scratch yang valid, praktis, dan efektif dalam meningkatkan kemampuan berpikir komputasi matematis peserta didik. Hal ini didukung dengan hasil skor validasi dari para ahli sebesar 3,10 dengan kategori valid. Respon peserta didik terhadap E-Modul diperoleh rata-rata skor 3,57 dengan kategori sangat praktis. Respon guru terhadap E-Modul diperoleh skor 3,40 dengan kategori praktis. Hasil gain score tes kemampuan pemecahan masalah matematis peserta didik sebesar 68,93 tergolong dalam kategori “efektif”. Maka dari hasil tersebut dapat dinyatakan bahwa E-Modul yang dikembangkan memenuhi kriteria valid, praktis dan efektif. Kata kunci: e-modul, project based learning, berpikir komputasi.DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp516-527